Effects of physical activity on lung function and quality of life in asthmatic children: An updated systematic review and meta-analysis - Jing, Zenghui; Wang, Xingzhi; Zhang, Panpan; Huang, Jinli; Jia, Yuanyuan; Zhang, Juan; Wu, Huajie; Sun, Xin (Frontiers in Pediatrics, 2023)
Background and objectives: The benefits of physical activity (PA) for asthmatic children were increasingly recognized, and as the design of studies on PA and asthma has become more refined in recent years, the latest evidence needed to be updated. We performed this meta-analysis to synthesize the evidence available from the last 10 years to update the effects of PA in asthmatic children. Methods: A systematic search was conducted in three databases, PubMed, Web of Science, and Cochrane Library. Randomized controlled trials were included, and two reviewers independently conducted the inclusion screening, data extraction, and bias assessment. Results: A total of 9 studies were included in this review after 3919 articles screened. PA significantly improved the forced vital capacity (FVC) (MD 7.62; 95% CI 3.46 to 11.78; p <0.001), and forced expiratory flow between 25% and 75% of forced vital capacity (FEF25-75) (MD 10.39; 95% CI 2.96 to 17.82; p =0.006) in lung function. There was no significant difference in forced expiratory volume in the first second (FEV1) (MD 3.17; 95% CI -2.82 to 9.15; p =0.30) and fractional exhaled nitric oxide (FeNO) (MD -1.74; 95% CI -11.36 to 7.88; p =0.72). Also, PA significantly improved the quality of life as assessed by the Pediatric Asthma Quality of Life Questionnaire (all items p <0.05). Conclusions: This review suggested that PA could improve FVC, FEF25-75, and quality of life in asthmatic children, but there was insufficient evidence of improvement in FEV1 and airway inflammation.